The Golden Yoke : the Legal Cosmology of Buddhist Tibet - French, Rebecca Redwood (Cornell University Press, 2019)
The Golden Yoke is a remarkable achievement. It is the first elaboration of the legal, cultural, and ideological dimensions of precommunist Tibetan jurisprudence, a unique legal system that maintains its secularism within a thoroughly Buddhist setting. Layer by layer, Rebecca Redwood French reconstructs the daily operation of law in Tibet before the Chinese invasion in 1959. In the Tibetans' own words, French identifies their courts, symbols, and personnel and traces the procedures for petitioning and filing documents. There are stories here from judges, legal conciliators, and lay people about murder, property disputes, and divorce. French shows that Tibetan law is deeply embedded in its Buddhist culture and that the system evolved not from the rules and judgments but from what people actually do and say. In what amounts to a fully developed cosmology, she describes the cultural foundation that informs the system: myths, notions of time and conflux, inner morality, language patterns, rituals, use of space, symbols, and concepts. Based on extensive readings of Tibetan legal documents and codes, interviews with Tibetan scholars, and the reminiscences of Tibetans at home and in exile, this generously illustrated, elegantly written work is a model of outstanding research. French combines the talents of a legal anthropologist with those of a former law practitioner to develop a new field of study that has implications for other judicial systems, including our own.